Infancias en crisis. Norah Lange y Silvina Ocampo - Julien Roger (Cuadernos LIRICO)
Cuadernos de infancia, by Norah Lange and Viaje olvidado, by Silvina Ocampo, both published in 1937, act as a break from childhood autobiographies of the 19th century and even of the first part of the 20th century. After wondering briefly about the reasons for this break, the article gives an insight into the way these two texts stage childhood in crisis- mainly through deaths, suicides, and murders. Lastly, we shall deal with the stylistic devices used by the authors to go beyond this crisis ; work on language, on focalization, and on time are the tools with which these narratives foil the crisis they are staging.